Elucidating the Doping Effect on the Electronic Structure of Thiolate‐Protected Silver Superatoms by Photoelectron Spectroscopy. (24th July 2019) - Kim, Kuenhee; Hirata, Keisuke; Nakamura, Katsunosuke; Kitazawa, Hirokazu; Hayashi, Shun; Koyasu, Kiichirou; Tsukuda, Tatsuya
Abstract: Gas‐phase photoelectron spectroscopy (PES) was conducted on [XAg24 (SPhMe2 )18 ] − (X=Ag, Au) and [YAg24 (SPhMe2 )18 ] 2− (Y=Pd, Pt), which have a formal superatomic core (X@Ag12 ) 5+ or (Y@Ag12 ) 4+ with icosahedral symmetry. PES results show that superatomic orbitals in the (Au@Ag12 ) 5+ core remain unshifted with respect to those in the (Ag@Ag12 ) 5+ core, whereas the orbitals in the (Y@Ag12 ) 4+ (Y = Pd, Pt) core shift up in energy by about 1.4 eV. The remarkable doping effect of a single Y atom (Y=Pd, Pt) on the electronic structure of the chemically modified (Ag@Ag12 ) 5+ superatom was reproduced by theoretical calculations on simplified model systems and was ascribed to 1) the weaker binding of valence electrons in Y@(Ag + )12 compared to Ag + @(Ag + )12 due to the reduction in formal charge of the core potential, and 2) the upward shift of the apparent vacuum level due to the presence of a repulsive Coulomb barrier between [YAg24 (SPhMe2 )18 ] − and electron. Abstract : Zentraler Austausch : Der Effekt von Heteroatom‐Dotierung auf die Superatomorbitale von [XAg24 (SR)18 ] − (X=Ag, Au) und [YAg24 (SR)18 ] 2− (Y=Pd, Pt) wurde mittels Gasphasen‐Photoelektronenspektroskopie untersucht. Die adiabatische Elektronenaffinität von [XAg24 (SR)18 ] wird beim Austausch des zentralen X + ‐Kations durch ein neutrales Y‐Atom um ca. 1.4 eV verringert.